1997
DOI: 10.1074/jbc.272.21.13849
|View full text |Cite
|
Sign up to set email alerts
|

The Thiol-dependent Reductase ERp57 Interacts Specifically with N-Glycosylated Integral Membrane Proteins

Abstract: The lumen of the endoplasmic reticulum contains a number of distinct molecular chaperones and folding factors, which modulate the folding and assembly of newly synthesized proteins and protein complexes. A subset of these luminal components are specific for glycoproteins, and, like calnexin and calreticulin, the thioldependent reductase ERp57 has been shown to interact specifically with soluble secretory proteins bearing Nlinked carbohydrate.Calnexin and calreticulin also interact with glycosylated integral me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 46 publications
6
96
1
Order By: Relevance
“…Ferrari and H.-D. So$ ling, unpublished work), and although ERp72, ERp57, PDIp and ERp28 have been reported to interact with peptides and\or malfolded proteins [10,[102][103][104][105][106][107][108], only for PDIp has the interaction been indicated to be direct [108].…”
Section: Peptide Bindingmentioning
confidence: 97%
See 1 more Smart Citation
“…Ferrari and H.-D. So$ ling, unpublished work), and although ERp72, ERp57, PDIp and ERp28 have been reported to interact with peptides and\or malfolded proteins [10,[102][103][104][105][106][107][108], only for PDIp has the interaction been indicated to be direct [108].…”
Section: Peptide Bindingmentioning
confidence: 97%
“…Redox-active-site [60,144] pendent manner [104,105], but probably only indirectly via interactions with calnexin or calsequestrin [106,107], as ERp57 itself lacks lectin-like properties [106]. This is in contrast with PDI, which interacts with proteins independently of their glycosylation status [65,104,107].…”
Section: Molecularmentioning
confidence: 99%
“…ERp57 has thiol-dependent reductase activity (29), cysteine-dependent protease activity (30,31), and is known to interact with glycoproteins in a manner that can involve forming complexes with either CXN and CRT (32)(33)(34). Three recent reports demonstrated that ERp57 is detected in association with class I molecules before peptide binding (26 -28).…”
Section: Association Of Erp57 Withmentioning
confidence: 99%
“…By applying chemical cross-linking techniques, it was demonstrated that in canine pancreatic microsomes, ERp57 associates only with glycosylated versions of membrane and secretory proteins [13,14]. This interaction depends upon glucose trimming and is transient [13], similar to the binding of calnexin and calreticulin.…”
mentioning
confidence: 99%